Revealing the effect of heat treatment on stress corrosion cracking behavior of Monel 400 alloy in hydrofluoric acid vapor environment. (1st May 2023) - Dai, Hailong; Shi, Shouwen; Tang, Jiahui; Guo, Can; Ning, Zuoliang; Chen, Xu
Abstract: The effect of heat treatment (HT) on the stress corrosion cracking (SCC) of Monel 400 alloy in hydrofluoric acid (HF) vapor was investigated through cracking crystallographic analysis. The SCC resistance is ordered as 750 °C-HT > AR > 850 °C-HT > 950 °C-HT > 1050 °C-HT, while the SCC failure mechanism is similar which is active dissolution-slip tearing. HT increases grain size and reduces residual strain, and large grains promote both slip and active dissolution, all contributing to higher SCC susceptibility. In addition, residual strain accelerates corrosion degradation, which counteracts the beneficial effect of fine grain on SCC resistance. Data availability: The raw/processed data required to reproduce these findings cannot be shared at this time due to technical or time limitations. They can be provided on request. Highlight: SCC performance of Monel 400 alloy in HF vapor is regulated by heat treatment. The effect of heat treatment is revealed through crystallographic analysis. Larger grain is harmful to SCC by accelerating mechanical and chemical degradation. High residual strain counteracts the benefits of fine grains on SCC resistance. Such mechanisms well explain the discrepancy in SCC behavior in the literature.